A Critical Analysis of Humanism Philosophy in Education Policy in the Vuca Era - Laksmi, Putu Putri Dena; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The demand for humanistic policies in the VUCA era has exposed many stakeholders to serious threats, particularly within the education sector. Rapid changes, biased information, policy uncertainty, and complex problem-solving workflows pose distinct challenges for educational policymakers. This study aims to analyze existing educational policies through the lens of humanistic philosophy. By identifying the gap between policy and practice, this research offers recommendations for improvement. This is crucial to ensure that educational policies remain relevant to contemporary societal needs. This study employs a qualitative approach utilizing a literature review. The collected data is analyzed to identify discrepancies between policy and practice. The analysis of educational policies through a humanistic lens highlights the importance of aligning policies with the needs of a more critical and adaptive society in the current era. By identifying the gap between policy and practice, this research provides recommendations to assist in creating a better and more responsive education system. This study recommends that educational policies become more inclusive and responsive to societal needs. This includes involving the community in decision-making processes and adapting the curriculum to reflect humanistic values.